Vegetable value chains during the COVID- 19 pandemic in Ethiopia: Evidence from cascading value chain surveys before and during the pandemic - Hirvonen, Kalle; Mohammed, Belay; Tamru, Seneshaw; Abate, Gashaw T.; Minten, Bart (International Food Policy Research Institute, 2021)
We combine in-person survey data collected in February 2020 (i.e., just before the pandemic was declared) with phone survey data collected in March 2021 (i.e., one year into the pandemic) and August 2021 (i.e., approximately 18 months into the pandemic) to study how vegetable value chains in Ethiopia have coped with the COVID-19 pandemic. Focusing on the major vegetable value chain connecting farmers in East Shewa zone to consumers in Addis Ababa, we applied a cascading survey approach in which we collected data at all levels of the value chain: vegetable farmers, urban wholesalers, and retailers.